Evaluation of the knowledge, attitudes and behaviors of pre-school teachers on oral and dental health in the city center of Trabzon - Özgül Baygın; Ezgi Baltacı; Tamer Tüzüner; Fatih Mehmet Korkmaz (European Oral Research)
PurposeEducators can also contribute to the prevention of early childhood caries (ECC)by educating children about oral diseases and hygiene practices. The aim of thisstudy was to assess the knowledge, attitudes, and behaviors of pre-school teachersconcerning oral and dental health in Trabzon.Subjects and methodsThe study was carried out with 226 pre-school teachers in the city center usinga self-administered questionnaire to evaluate their knowledge, attitudes, andbehaviors concerning the oral and dental health of children.ResultsOnly 29.8% of the respondents had a prior dental education. Although 83% of theteachers said that regular visits to the dentist were effective for caries prevention,only 13.2% said that they made regular visits to a dentist. Approximately 65.8%of the teachers agreed that fluoride strengthens tooth enamel and 35.1% of theteachers said that there were oral health activities in their schools. Additionally,74.6% of teachers said that they would participate in dental education aboutchildren’s oral health in the future.ConclusionPreventive dental health program could be implemented including the properbehaviors related to the importance and treatability of primary teeth, first toothcleaning, dental visits, the use of fluoride toothpaste, and oral hygiene into the preschoolteachers’ undergraduate education programs in the future. This programshould be repeated at certain intervals for the prevention of ECC.